Reações de ciclocondensação de cianoacetoidrazida com enonas halometil-substituídas - Moreira, Dayse das Neves (2008)
The synthesis of thirteen 3-(R1), 4-(R2) and 5-(R3)-substituted 1-cyanoacetyl-5-hydroxy-4,5-dihydro-1H-pyrazoles from the cyclocondensation reaction of 4-alkoxy-3-alken-2-ones [R3C(O)C(R2)=C(R1)(OR), where R3 = CF3, CCl3, CHCl2, CO2Et; R2 = H, Me; R1 = H, Me, Et, Pr, Pentyl, c-Hexyl, Ph, and R = Me, Et] with cyanoacetohydrazide is reported. This reaction was carried out in different methodologies, firstly using water like solvent and following with ionic liquid ([BMIM]BF4). The results showed that when the ionic liquid was used as reaction media, the reaction time was drastically decreased and the yield was improved. 4,5-Dihydropyrazole (R1 = Me, R2 = H, R3 = CF3) was used as an important building block to the synthesis of cyanoenaminopyrazole from the condensation reaction with N,N-dimethylformamide dimethyl acetal. Benzilidene cyanoacetohydrazide was also employed to the synthesis of a series of seven 1- benzilidenepyrid-2-ones from the cyclocondensation reaction with 4-alkoxy-1,1,1-trifluoro-3-alken-2-ones [CF3C(O)C(R2)=C(R1)(OR), where R2 = H, Me; R1 = Me, Pr, Butyl, c-Hexyl, Ph, 4-MePh, e R = Me, Et]. The attainment of these compounds was only possible when the reaction was carried out in ionic liquid [BMIM]BF4.